2007
DOI: 10.1108/10610420710751573
|View full text |Cite
|
Sign up to set email alerts
|

Price endings and consumer segmentation

Abstract: Price Endings and Consumer Segmentation -Research Paper Abstract PurposeTo investigate the area of price endings to determine which groups of consumers are more likely to respond with 9-endings as opposed to round-endings. MethodologyA questionnaire was developed that tested respondents' use of 9-endings as opposed to roundendings dependent on classification by gender and age. Respondents were required to estimate the price they would be expected to pay in stores for six products. This methodology enabled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
14
0
6
Order By: Relevance
“…Additionally, Blattberg and Wisniewski (1989) did another extensive analysis of scanner data from a major supermarket also showed that more than 80% of the prices in the shops ended with numeral nine. A more recent research by Harris and Bray (2007) discovered that 64% of prices in the UK ended with a digit-nine and other researches by Bergen et al (2004) with internet-based shops also showed a nine-ending price. Also, Schindler (2001) and Guéguen and Legoherel (2004) found the presence of the same trends in the retail shops in western economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Blattberg and Wisniewski (1989) did another extensive analysis of scanner data from a major supermarket also showed that more than 80% of the prices in the shops ended with numeral nine. A more recent research by Harris and Bray (2007) discovered that 64% of prices in the UK ended with a digit-nine and other researches by Bergen et al (2004) with internet-based shops also showed a nine-ending price. Also, Schindler (2001) and Guéguen and Legoherel (2004) found the presence of the same trends in the retail shops in western economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cost of importing the pennies was less than the profit made on sales of the newspaper. It has been explained by some researchers (Burns, 1995;Hower, 1943) as cited in Harris and Bray (2007), that odd-ending pricing was brought into practice for operational reasons with the introduction of cash registers in 1879. The reason behind this was assumed to be that shop proprietors wanted to make sure that tills were open for every transaction to prevent the dishonest cashiers from pocketing the cash.…”
Section: History Of Practice Of Psychological Pricing Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Atliekant sociologinius tyrimus amžius -svarbi ir įprasta demografinė charakteristika. Paprastai bandoma apimti platų amžiaus tarpsnį (nuo paauglystės iki senatvės), jį vėliau skaidant ir analizuojant atskirais intervalais, pavyzdžiui, 15-29 m., 30-44 m. ... (Harris, Bray 2007), iki 20 m., 20-30 m. ... (Kaynak, Kara 2001Seock, Baylei 2008) ar panašiai -20-29 m., 30-39 m. ... (Okazaki, Hirose 2009). Keblumų atsiranda lyginant greta esančius intervalus dėl galimos jų sankirtos: mokslinėje literatūroje nurodoma, kad chronologinis žmogaus amžius gali nesutapti su jo "pažintiniu" amžiumi, kai keturiasdešimtmetis jaučiasi kaip trisdešimtmetis (Stephens 1991 šios priežasties racionaliau tiriamąją imtį skaidyti kartomis, kurios nei teoriškai, nei praktiškai negalėtų turėti susiliejimo erdvės, niveliuojančios skirtumus.…”
unclassified